Використання індивідуального інструмента для кінематичного вирівнювання осі кінцівки під час ендопротезування колінного суглоба (випадок із практики) - Головаха, Максим Леонідович; Бондаренко, С. А.; Golovakha, M. L.; Bondarenko, S. A. (My University, 2023)
Objective. To give a clinical example where, under the conditions of gonarthrosis, the patient underwent preoperative planning using modern technologies of three-dimensional modulation; outline the stages of individual instrument preparation and for kinematic alignment of the axis of the lower extremity and installation of knee joint endoprosthesis components. Methods. A 69-year-old patient was diagnosed with stage IV right-sided gonarthrosis. For preoperative planning, a computer tomography of the lower extremities was performed in the position of full extension in the knee joints and neutral rotation of the feet (slice thickness 1 mm). A 3D model of the lower extremities was built in the "STL" format in the RadiAnt DICOM Viewer Version 2021.2 program and imported into the FreeformPlus program. Preoperative planning was performed according to the principle of kinematic alignment to restore the constitutional axis of the limb and the inclination of the knee joint plane. The main stages of preparation of an individual instrument and carrying out operative intervention are given. Functional evaluation was performed before and after the operation at different stages according to the EuroQol-5D, KSS, HSS scales and a six-step functional test. Results. Individual navigation made it possible to precisely carry out resections of the articular ends and perform the planned kinematic alignment of the limb. According to the EuroQol-5D scale, the improvement of the patient's quality of life was determined, starting from the 3rd day after the operation. According to the KSS scale, an excellent result (85 points) was obtained 6 weeks after the surgical intervention, which remained after 3 months. The evaluation of the result of endoprosthesis according to the HSS scale after 6 weeks was 36 points, after 3 months — 38 points. Conclusions. A clinical example of the use of an original individual instrument for knee endoprosthesis showed the main advantages of the method — accurate installation of endoprosthesis components according to the preoperative design, which ensured high patient satisfaction and a good functional result. Key words. Knee joint, gonarthrosis, total arthroplasty, patient specific instrument. Мета. Навести клінічний приклад, де за умов гонартрозу пацієнтові виконано передопераційне планування з використанням сучасних технологій тривимірного модулювання; викласти етапи підготування індивідуального інструмента для кінематичного вирівнювання осі нижньої кінцівки та встановлення компонентів ендопротеза колінного суглоба. Методи. У пацієнтки віком 69 років встановлено діагноз: правобічний гонартроз IV стадії. Для передопераційного планування виконано комп’ютерну томограму нижніх кінцівок у положенні повного розгинання в колінних суглобах і нейтральній ротації стоп (товщина зрізів 1 мм). Побудовано 3D‒модель нижніх кінцівок у форматі «STL» у програмі RadiAnt DICOM Viewer Version 2021.2 та імпортовано в програму FreeformPlus. Передопераційне планування виконано за принципом кінематичного вирівнювання для відновлення конституціональної осі кінцівки та нахилу площини колінного суглоба. Наведено основні етапи підготовки індивідуального інструмента та проведення оперативного втручання. Функціональне оцінювання виконано до операції та після неї на різних етапах за шкалами EuroQоl-5D, KSS, HSS та функціональною пробою шести кроків. Результати. Індивідуальна навігація дала змогу точно провести зпили суглобових кінців і виконати відповідне до запланованого кінематичне вирівнювання кінцівки. За шкалою EuroQоl-5D визначено покращення якості життя пацієнтки, починаючи з 3-ї доби після операції. За шкалою KSS отримано відмінний результат (85 балів) через 6 тижнів після хірургічного втручання, який зберігся й через 3 міс. Оцінка результату ендопротезування за шкалою HSS через 6 тижнів склала 36 балів, через 3 міс. — 38 балів. Висновки. Клінічний приклад використання оригінального індивідуального інструмента для ендопротезування колінного суглоба показав основну переваги методу — точне встановлення компонентів ендопротеза згідно з передопераційним проєктуванням, що забезпечило високу задоволеність пацієнта та добрий функціональний результат.
Use of an individual tool for kinematic alignment of the limb axis during knee arthroplasty (clinical case)
Keywords: колінний суглоб; гонартроз; ендопротезування; індивідуальний інструмент